Republic of Kazakhstan : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kazakhstan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global financial crisis led to an abrupt halt in credit growth, exposed underlying vulnerabilities in the banking sector, and impaired GDP growth in Kazakhstan. Executive Directors commended the authorities for their prudent macroeconomic policies and swift response to the financial crisis. They stressed the urgency of implementing the bank resolution strategy accompanied by full assessment of recapitalization needs and improvements in the regulatory and supervisory frameworks. Directors highlighted the need for a well-capitalized and well-regulated financial system in facilitating economic diversification, and urged sustained efforts to improve governance and the business environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet